156 Patient Reported Outcomes Measures Following Mitral Valve Repair: Minimally Invasive Video-Assisted Compared to Sternotomy. (3rd June 2016) - Whiteley, Jennifer; Jones, Sion; Exarchou, Klare; Palmer, Ken; Modi, Paul
Abstract : Objectives: There is a paucity of evidence regarding patient reported outcomes following mitral valve repair (MVP). Our aim was to compare these in patients having minimally invasive (MI) andsternotomy (St) approaches. Method: Between August 2011 and June 2014, 235 patients underwent MVP, of which 71 (30.2%) had a MI procedure performed through a 5–6 cm right anterior minithoracotomy. We adapted the Composite Physical Function questionnaire to retrospectively assess post-operative quality of life in 3 domains (scores were converted into a 0–100 scale) -– Recovery Time (higher score indicated longer recovery time); Pain (higher score indicated increased pain) and Treatment Satisfaction (higher score indicated improved satisfaction). The scores were risk-adjusted using pre-operative characteristics (age, gender, urgency, Logistic EuroSCORE). Data are reported as median (interquartile range). Results: The response rate was 70.6% (n = 166) of which 51(30.7%) underwent MI repair. Comparing St to MI, 14.8% vs 35.3% resumed 'normal activities' within 6 weeks of their operation (p = 0.003). The risk-adjusted Recovery Time domain results for St vs MI were 54.4 (44.4, 69.6) vs. 44.9 (26.7, 58.0), p < 0.001; likewise, the risk-adjusted Pain domain results were 31.8 (16.9, 50.0) vs. 21.9 (12.4, 32.8), p = 0.03; and the risk-adjusted Treatment Satisfaction domain results were 98.1 (83.9, 99.9) vs. 98.3 (88.9, 100.0), p = 0.25. Comparing St to MI, 53.0% vs. 78.4% reported that they were 'Very Satisfied' with the appearance of their scar (p = 0.002). Conclusion: Minimally invasive mitral valve repair speeds recovery, reduces pain and improves cosmesis compared to a sternotomy approach. Both approaches score highly on patient satisfaction.